2005
DOI: 10.1038/nrg1659
|View full text |Cite
|
Sign up to set email alerts
|

Molecular clocks: four decades of evolution

Abstract: During the past four decades, the molecular-clock hypothesis has provided an invaluable tool for building evolutionary timescales, and has served as a null model for testing evolutionary and mutation rates in different species. Molecular clocks have also influenced the development of theories of molecular evolution. As DNA-sequencing technologies have progressed, the use of molecular clocks has increased, with a profound effect on our understanding of the temporal diversification of species and genomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
257
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 346 publications
(268 citation statements)
references
References 105 publications
3
257
0
5
Order By: Relevance
“…The first chimpanzee fossil, for example, was only just reported in 2005 (1). As recently as the mid-1960s (2), the African apes were considered to be distant relatives of the human lineage, but subsequent molecular phylogenetic analyses have shown that the chimpanzee and human are sister species and have led to a revision of the age of their divergence (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Currently, the earliest unequivocal upright hominids at 4.2 millions of years ago (Ma) provide the minimum age for human-chimpanzee divergence (14), and some recently proposed early hominids dated between 5 and slightly more than 6 Ma are thought to provide an estimate close to the actual species divergence (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first chimpanzee fossil, for example, was only just reported in 2005 (1). As recently as the mid-1960s (2), the African apes were considered to be distant relatives of the human lineage, but subsequent molecular phylogenetic analyses have shown that the chimpanzee and human are sister species and have led to a revision of the age of their divergence (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Currently, the earliest unequivocal upright hominids at 4.2 millions of years ago (Ma) provide the minimum age for human-chimpanzee divergence (14), and some recently proposed early hominids dated between 5 and slightly more than 6 Ma are thought to provide an estimate close to the actual species divergence (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…However, studies using molecular data have yielded disparate values as well (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13), because of differences in the number of genes used, types of substitutions (synonymous, noncoding, and nonsynonymous) analyzed, calibration points used, and statistical methods used (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Furthermore, current estimates of C.I.s of molecular divergence times fail to consider a comprehensive set of factors contributing to variance, such as a limited number of genes (gene sampling error), a limited number of sites for each gene (variance contributed by sequence divergence-estimation procedures), rate differences among lineages, and inherent uncertainty in the time used for calibrating lineage-specific and relaxed molecular clocks (21,22).…”
mentioning
confidence: 99%
“…The established ages of the islands, in concert with recent molecular clock advances, facilitate increasingly accurate time estimates of past speciation events. They provide powerful tools for unravelling the evolutionary history and impacts of geology on insular species radiations [3][4][5] . While the relatively young current high islands range in age from 0.5 (island of Hawaii) to 4.7 Myr ago (island of Kauai), the oldest of the persisting Northwestern Hawaiian Islands (NWHI), Kure atoll, is estimated at 29.8 Myr ago 2,3 .…”
mentioning
confidence: 99%
“…Reconstruction of phylogenetic or evolutionary trees by comparison of biomolecular sequences became an established method through the works of Walter Fitch, Emanuel Margoliash, and Margaret Dayhoff in the 1960s, and the evolutionary clock (Kumar 2005) became an established tool in evolution research for dating speciation events. In vitro evolution of RNA molecules from bacteriophages was initiated by Sol Spiegelman in the 1960s (Spiegelman 1971).…”
Section: Historymentioning
confidence: 99%
“…Molecular phylogenetics reconstructs the tree of life from present-day sequences of species (Graur and Li 2000) in which the proper alignment of sequences is an important part of the procedure (Mount 2004). Comparing sequences from vertebrates reveals the molecular clock of evolution (Morgan 1998;Kumar 2005;Takahata 2007), which implies that the number of single point mutations per nucleotide site and time is approximately constant for a given protein molecule. Further investigations have shown substantial vagaries of the clock, but in the age of genomics, the molecular clock turned out to be a valuable device for dating historical events.…”
Section: Overviewmentioning
confidence: 99%